Rare leiomyosarcoma in a burn scar - Inampudi Sravya; Joseph Thomas; N C Sreekumar; Bhavna Nayal (Wolters Kluwer Medknow Publications, 2019)
Leiomyosarcomas presenting as a cutaneous malignancy in a burn scar are rare due to scarce mesenchymal elements within the cutaneous tissues. We here present a case of a 73-year-old woman with a past history of burns, came with a recurrent ulceroproliferative lesion in the right lumbar region over previous burn scar. She had a history of a similar lesion in the same region 1 year ago, for which wide local excision and grafting were done, and histopathology revealed as sarcomatoid carcinoma. Examination revealed multiple right axillary lymph nodes. Evaluation was done with contrast-enhanced computed tomography to rule out systemic metastasis. She was managed surgically with wide local excision, right axillary dissection, and split skin grafting. She had aggressive local recurrence along with lung metastasis within 6 months and was lost to follow-up. This report presents the second case of leiomyosarcoma arising in a burn scar on the right flank.